Genealogias e histórias de antepassados em Galileia, de Ronaldo Correia de Brito - Andre de Souza Pinto (2016)
The present dissertation, which analyzes the novel Galileia (2009), by Ronaldo Correia de Brito, has as its main objective to study the familiar genealogy fictionalized by the writer. In this work the history of the Rego Castro family is examined, set in Galileia, besides other Britos texts. In Galileia, the writer appropriates the biblical text, rewriting and modifying it. The myths of the back country environment, such as the stories recovered from its traditions, are in conformity with Britos narrative, composingthe structure and the warp of it. The genealogic analysis of the Rego Castro family allows us to establish links between Britos novels and tales, whose familiar stories, with reports, ruined houses or families, are remarkable. The novel Galileia is characterized, still, by the possibility of leaving a glimpse of self-awareness and selfreflexivity which, in the references to the act of rewriting, such as the strategy of appropriating a biblical narrative and myths from the backwoods, whose referencesintersect in the narrative, display the fictional construction of the stories told. The rewriting, citation and literary appropriation in the novel were studied, based on the theoretical assumptions of Antoine Compagnon, Umberto Eco, Michel Schneider and Ricardo Piglia.